Analisis Alat Peraga Terhadap Motivasi Belajar IPA Kelas V SD Kristus Raja II Kota Sorong - Jasinta Maria Adolfina Stibies; Anis Alfian Fitriani; Ahmad Yulianto (Program Studi PGSD Universitas Madako Tolitoli, 2023)
Teaching aids not only help the teaching and learning process and make the classroom fun, but also motivate students to learn. In grade V of SD YPPK Kristus Raja II Sorong City, the purpose of this study was to find out how the use of teaching aids affects students' desire to learn about the human digestive system. This research is a descriptive quantitative type involving 18 students. Data was collected through a validated questionnaire. The reliability test showed a score of 0.922, which means highly reliable. The analyzed data showed normal distribution, and the hypothesis test results showed the effect of teaching aids on students' desire to learn. As a result of the inferential statistical analysis, it is known that H1 is accepted and H0 is rejected, because tcount is greater than ttable, which is 40.5542 greater than 2.110. It is known that the use of teaching aids has an impact on students' desire to learn about the materials included in the human digestive system.